Implementasi Manajemen Berbasis Sekolah di SMP Negeri 2 Sumalata - Winda Mahmud; Roy Hasiru; Rierind Koniyo; Agil Bahsoan; Yulianti Toralawe (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the implementation of School-Based Management (SBM) at SMP Negeri 2 Sumalata, Sumalata District, North Gorontalo Regency, and to identify factors that influence its success. The study used a qualitative method with a descriptive approach and field research design (field research). Data collection techniques include interviews, observations, and documentation, while data analysis is carried out through the process of data reduction, data presentation (display), and drawing conclusions. The results of the study indicate that the implementation of SBM at SMP Negeri 2 Sumalata has covered several aspects, including curriculum management, students, finance, education personnel, facilities and infrastructure, school-community relations, and special services. However, its implementation is still not optimal. One of the main obstacles is the principal's supervision which has not been running effectively, thus affecting the level of teacher professionalism. Internal factors such as leadership, teacher motivation, and limited resources also affect the implementation of SBM as a whole.